Genetic divergence of indigenous pummelo genotypes (Research in Agriculture Livestock and Fisheries, 2016)
The genetic divergence was studied in33pummelogenotypes using D2 statistics and principal component analysis at Regional Agricultural Research Station, BARI, Akbarpur, Moulvibazar during 2012 to 2014. The genotypes were grouped into 5 clusters and the maximum number of genotypes was included in cluster IV and V and the minimum number in cluster I. The inter cluster distance in all of the cases were higher than the intra cluster distance indicating wider genetic diversity among the accessions of different groups. The highest inter-cluster distance was observed between cluster I and II followed by cluster II and V and the lowest between III and IV. The highest intra- cluster distance was observed for the cluster II and the lowest for the cluster III. For cluster II, the highest mean values for plant height (6.13m), individual fruit weight (1141.67g), fruit length (13.03 cm) and breadth (13.15 cm), number of segments per fruit (14.41), number and weight of seeds per fruit (123.67 and 50.41g), yield per plant (50.94 kg) were observed. The first axis largely accounted for the variation among the pummelo accessions (26.16%) followed by second axis (18.75%). The first 8 axes accounted 90.56 % of the total variation. The characters individual fruit weight (g) and weight of seeds per fruit (g) showing positive value in both the vectors contributed maximum towards divergence. Considering magnitude of genetic distance, contribution of different traits toward the total divergence, magnitude of cluster means for different traits and performance the genotypes of cluster I, II, and IV may be considered as parents for future hybridization program.Res. Agric., Livest. Fish.3(1): 37-43, April 2016